LOGISTICS APPROACH TO ORGANIZING THE ACTIVITIES OF A TERMINAL AND WAREHOUSE - Kobulov , Mukhammadjon (Techscience uz - Topical Issues of Technical Sciences, 2025)
The article under consideration herein explores contemporary approaches to the organization of terminal warehouse activities. A growing number of Russian enterprises are recognizing the importance of leveraging information support to enhance their operational efficiency. In this regard, the author of the paper under review has considered and analyzed the main approaches to the organization of warehousing activities, such as system and process approaches.